Da’wah values in the opening ceremony video of the World Cup Qatar 2022 (A John Fiske’s semiotic analysis) - Fikri Fikri; Dyta Septiyatik; La Ode Andri; Mudhiah Umamah (Islamic Communication Journal, 2023)
This study aims to identify the three levels of semiotics based on John Fiske's semiotic theory and to explain da'wah values in the opening video of the Qatar 2022 World Cup. This study uses a descriptive method with an interpretive qualitative research data approach. The data were collected by watching the video and taking screenshots. The data were categorized and analyzed based on John Fiske's semiotic theory. The results show that there are da'wah values including faith, sharia, and morals. In addition, the three levels of signs conveyed by John Fiske are reflected in the costumes of actors, singers who cover their genitals (reality level), angels, lighting, music, sounds (representative level), love for animals or other living things, mutual respect between religions, races. culture, hospitality, and Arab nationalism (ideology level). As the opening ceremony of the World Cup is a moment where all eyes will be on, that was a great opportunity to deliver the ideology and broadcast the da'wah values. Therefore, the da'wah values can be shared massively compared to when da'wah is delivered orally.  This study contributes to the development of a culture-based da'wah model, which is in accordance with the principles of a friendly and universal Islam. ***Penelitian ini bertujuan untuk mengidentifikasi tiga level semiotika berdasarkan teori semiotika John Fiske dan menjelaskan nilai-nilai dakwah dalam video pembukaan Piala Dunia Qatar 2022. Penelitian ini menggunakan metode deskriptif dengan pendekatan data penelitian kualitatif interpretatif. Data dikumpulkan dengan menonton video dan mengambil screenshot. Data dikategorikan dan dianalisis berdasarkan teori semiotika John Fiske. Hasil penelitian menunjukkan bahwa terdapat nilai-nilai dakwah yang meliputi akidah, syariah dan akhlak. Selain itu, tiga level tanda yang disampaikan John Fiske tercermin dari kostum aktor, penyanyi yang menutup aurat (level realitas), angle kamera, tata cahaya, musik, suara (level representasi), kasih sayang kepada hewan atau makhluk hidup lainnya, saling menghormati antar agama, ras, budaya, keramahtamahan, dan nasionalisme Arab (level ideologi). Karena, upacara pembukaan Piala Dunia merupakan momen di mana semua mata akan tertuju, maka hal tersebut merupakan kesempatan yang baik untuk menyampaikan ideologi dan menyebarkan nilai-nilai dakwah. Dengan demikian, nilai-nilai dakwah dapat disebarkan secara masif dibandingkan dengan dakwah yang disampaikan secara lisan. Kajian ini berkontribusi bagi pengembangan model dakwah berbasis kebudayaan, yang sesuai dengan prinsip Islam yang ramah dan universal.